The Retrospective Evaluation of the Patients in Pediatric Cardiac Intensive Care Unit of Cardiac Surgery Center - Erkut Öztürk; Taner Kasar; Okan Yıldız; Alper Güzeltaş; Sertaç Haydin (Galenos Yayinevi, 2019)
Introduction:In this study, demographic and epidemiologic features, clinic and prognosis of patients admitted to the pediatric cardiac intensive care (PCICU) unit of a cardiac surgery center were analysed retrospectively.Methods:Patients followed in the PCICU between January 2017 and January 2018 were included in the study. Patient files were analysed for medical data. The patients were divided into 4 major categories as postoperative patients (group 1), patients followed after cardiac catheterization (group 2), patients followed due to arrythmias (group 3), and others (myocarditis, pneumonia, tamponade) (group 4). The demographic variables, such as age and gender, echocardiographic diagnosis, kind and condition of the transfer, reason for PCICU follow-up, and discharge status were evaluated in detail.Results:Eighty hundred ninety five patients were followed in the PCICU during the study period.The median age was 5.5 months (1 day-18 years). 53% of patients (n=474) were male and 47% (n=421) were female. The ortanca weight of the patients was 7.2 kg (1.8-80 kg). 16% of the patients were younger than 1 month of age and 54% of the patients were under the age of 6 months. 12% (n=107) of the patients had a diagnosis of a genetic condition such as Down syndrome, DiGeorge syndrome, etc. 40% of the patients were non-residents. 25% was transferred by air ambulance or ground ambulance. 22% of the patients were foreigners. There were 610 patients in group 1, 130 patients in group 2, 55 patients in group 3, and 100 patients in group 4. The RACHS-1 scores in group 1 were as follows: 0.8% undetermined, 11.2% category 1, 42.9% category 2, 29.6% category 3, 12.6% category 4,(-) category 5, and 2.6% category 6. Overall mortality was 5.9% (n=53) and morbidity was 22% (n=197).Conclusion:We believe that by the means of this kind of epidemiological studies, we may detect the types of cardiac problems in children who needed intensive care follow-up and help to decrease mortality and morbidity in childhood due to congenital cardiac diseases in our country.